Commercial varieties of European plums grown in Hungary, a comparison of promising foreign varieties with the widely grown traditional ones - Kovács, Sz.; Molnár, Á.; Szenci, Gy.; Tóth, M. (International Journal of Horticultural Science, 2012)
Observations and investigations performed in laboratory at several growing sites over a period of many years are summarised on established plum varieties as well as on new promising ones concerning their marketing value. The ripening period of plum varieties was enlarged substantially with the appearance of new varieties of extra late maturity (‘Elena’, ‘Tophit’, ‘Presenta’). The new varieties did not alter the traditional colour, more or less long, violet or blue character of the plum. The most known type, ‘Besztercei szilva’ with its accustomed taste was followed by the new varieties ‘Katinka’, ‘Tegera‘, ‘Hanita’ and ‘Presenta’. The fruit size are largely of the medium category, except the early ripening small ‘Katinka’, whereas the larger and attractive (~60 g) fruits are represented by the late ripening ‘Tophit’ and ‘Empress’. The stone/fruit ratio was lowest in 3% (‘Tophit’) and 6% (‘Besztercei Bt. 2’, ‘Hanita’, ‘Jojo’, ‘ ‘Čačanska rana’) at the other end of the scale. The width and thickness of the fruit fl esh between 28 mm (‘Besztercei szilva’) and 43-44 mm (‘Empress’, ‘Tophit’). The fi rmness of the fruit fl esh excelled in the late maturity varieties ‘Presenta’ and ‘Tophit’ (~4 kg/cm2). Water soluble solids were 12-13 Brix% (‘Čačanska rana’, ‘Katinka’, ‘Silvia’) and 20 Brix% (‘Presenta’, ‘Tophit’), whereas titrated acids are found between 0.2% (‘Besztercei Bt. 2’) and 1.2% (‘Tegera’).